Progettare "paesaggi di limite" - Valentini, Antonella (Scuole di dottorato, 2005)
The volume deals with the theme of urban landscape design, taking into account in particular the experience of "green belts" and "green wedges". The limit landscape project carries out experimentations in the peri-urban territories of Florence and is not aimed at the reconstruction of ideal limits to the city; it is rather aimed at offering instances of rebalancing, connotation and regenerating typical of border territories experiencing indetermination of identity characters and strong reductions in landscape quality.